The Effect of Work Motivation and Job Satisfaction on Employee Performance Through Employee Engagement as an Intervening Variable - Nurlinda, RA.; Hidayat, Herman (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The purpose of this study was to determine the direct effect of Work Motivation and job satisfaction on Employee engagement, to determine the direct effect of Work Motivation, job satisfaction, and Employee engagement on Employee Performance. As well as the indirect effect of Work Motivation and job satisfaction on Employee Performance through Employee engagement. Data collection was carried out using a questionnaire distributed online using Google from through social media such as WhatsApp. The sample in this study were all permanent employees of the telecommunications company PT RIZKI PRIMA SAKTI totaling 170 people. This study used Smart Pls to analyze the data. From the data analysis, it was found that Work Motivation did not affect Employee engagement, Job satisfaction had a positive effect on Employee engagement. Furthermore, Work Motivation did not affect Employee Performance, but Job satisfaction and Employee engagement had a positive effect on employee performance. Work Motivation did not affect Employee Performance through Employee engagement, but job satisfaction affected Employee Performance through Employee engagement. Based on the research results, companies need to pay attention to Work Motivation by providing full support to employees so that they get job satisfaction so that employees will feel engaged in working and ultimately employees will give their best performance for the company.